Home based primary care for elderly in an Indian city - Kapil Bhatia; Pallavi Bhatia (Al Ameen Medical College, 2021)
Background: With increased age there is decreased quality of life due to increased spur in disabling chronic noncommunicable diseases. Every country should prepare themselves to meet the growing challenge of caring for its aged population. This increase in health care challenge for aged makes the government to find alternate care giving strategies. One such strategy is to provide home based physical care to the aged Aim: Study was undertaken to know the perception of aged persons care taker about the need of home based care services for chronically ill patients above the age of 60 years. Material & Methods: Study was carried out at different localities of Pune for the cancer patients who were previously admitted in a tertiary care hospital. 50 care takers of the patient were given the questionnaire by e mail. Results: Among the various responses maximum assistance was required in assisted bed movements accounting to 62%, this was followed by 60% of patients requiring assistance in walking. Conclusion: With limited elderly specialized centers & expenses involved in the hospitals, home base care appears to be a good alternative for the elderly as a cost effective approach leading to patient's satisfaction.